Effects of pre-partum dietary crude protein level on colostrum fat globule membrane proteins and the performance of Hu ewes and their offspring - Wang, Zhongyu; Zhang, Nana; Li, Fadi; Yue, Xiangpeng (Frontiers in Veterinary Science, 2022)
Dietary proteins play important roles in the growth and reproduction of sheep, and the ewe’s demand for proteins increases dramatically during late pregnancy. This research aimed to investigate the effect of dietary crude protein (CP) levels during late pregnancy on colostrum fat globule membrane (MFGM) protein and the growth performance of Hu sheep and their offspring, and provide a reference for the protein intake of ewes during late pregnancy. A total of 108 multiparous Hu sheep (45.6 ± 1.18 kg) were selected for this study, then 60 pregnant ewes confirmed by B-scan ultrasonography were randomly divided into three treatments (20 ewes/treatment) and fed by total mixed ration pellet with CP levels at 9.00% (LP), 12.0% (MP), and 15.0% (HP) during late pregnancy, respectively. The weight and dry matter intake of ewes during late pregnancy were recorded to calculate the average daily gain (ADG) and feed conversion ratio (FCR). Twin lambs were weighed on days 0, 7, 14, 30, 60, and 180 after birth to calculate ADG. Meanwhile, the colostrum of ewes was collected within 12 hours after delivery. The colostrum MFGM proteins were identified and quantified by the isobaric tag for relative and absolute quantification (iTRAQ) coupled with liquid chromatography-tandem mass spectrometry methods. In addition, biological functions of differentially expressed proteins (DEPs) were annotated by Gene Ontology annotation and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis. The results revealed that a 15.0% CP level had significant effects on the BW of lambs on days 0, 7, and 30 (P < 0.05). Notably, a total of 1529 MFGM proteins were identified and 286 DEPs were found among three treatments. Functional analysis showed that DEPs were mainly involved in cell growth, differentiation, and tissue repair, and involved in metabolic pathways, such as the porphyrin and chlorophyll metabolism pathways. In this study, lambs in HP treatment had better growth performance; moreover, dietary 15.0% CP level also affected the colostrum MFGM proteins composition of Hu ewes. These observations can facilitate future studies on the feeding regimen of ewes during late pregnancy.